2021
DOI: 10.3390/antiox10081277
|View full text |Cite
|
Sign up to set email alerts
|

Young Shoots of White and Red Headed Cabbages Like Novel Sources of Glucosinolates as Well as Antioxidative Substances

Abstract: Most literature data indicate that the diet rich in plant products reduces the risk of developing chronic non-communicable diseases and cancer. Brassica vegetables are almost exclusively synthesizing glucosinolates. Glucosinolates are higher in sprouts than in mature plants, being related to the activity of the specific myrosinase involved in the degradation of glucosinolates during developmental stages. This study compares the content of total glucosinolates with their profile and, rare in the literature, als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In addition to assessing the accumulation of different cabbage pigments, this study also identified important defensive GLS involved in the defense responses against biotic and abiotic stresses, which have been reported to be widespread in cabbage and other cruciferous plants [37][38][39]. Among those GLS in different developmental stages, the content of GLS in the outer leaves showed dynamic fluctuations (Figure 6), which may be due to the influence of environmental factors on the accumulation of GLS in different developmental stages.…”
Section: Comparative Analysis Of Gls In Cabbage Development Period-ec...mentioning
confidence: 92%
“…In addition to assessing the accumulation of different cabbage pigments, this study also identified important defensive GLS involved in the defense responses against biotic and abiotic stresses, which have been reported to be widespread in cabbage and other cruciferous plants [37][38][39]. Among those GLS in different developmental stages, the content of GLS in the outer leaves showed dynamic fluctuations (Figure 6), which may be due to the influence of environmental factors on the accumulation of GLS in different developmental stages.…”
Section: Comparative Analysis Of Gls In Cabbage Development Period-ec...mentioning
confidence: 92%
“…fruit contains a variety of bioactive substances, such as polysaccharides, polyphenols, amino acids, nucleotides, triterpenoid acids, alkaloids and other nutrients, and has antioxidant and other physiological functions [35]. Cabbage contains glucosinolates, which not only has good antioxidant capacity but also plays an important role in cancer prevention [36]. Lotus root contains phenolic compounds, which have strong antioxidant and scavenging capacities against oxidative factors, so it will become a potential material for extracting antioxidants [37].…”
Section: Plant Antioxidantsmentioning
confidence: 99%
“…The growing popularity of young shoots is not only due to their nutritional importance, but also to their fascinating organoleptic characteristics. A number of factors, such as the rapid reduction of land sources, changes in lifestyle and eating habits, as well as the need for sustainable food production, have increased the interest in micro-scale vegetable production for the ready-to-eat meal market [8,9]. In the United States and European countries, microgreens have begun to appear in some grocery stores, mainly large supermarkets.…”
Section: Introductionmentioning
confidence: 99%